Comparative phenotypic analysis of lymph node cells in mice after infection or vaccination with normal or ultraviolet-attenuated cercariae of Schistosoma japonicum or S. mansoni - Lii, Fang-Li; Gui, Ming; Filsinger, Sabine; Hänsch, Gertrud Maria; Ruppel, Andreas (Parasite immunology, 1995)
Mice were infected with 200 untreated or vaccinated with 500 ultraviolet-attenuated cercariae of either Schistosoma japonicum or S. mansoni. For three weeks, cell numbers in axillary and mediastinal lymphnodes were counted and cell populations typed by cytofluorometry. In the axillary lymphnodes, numbers of B-cells and CD3+CD4+ T-cells but not CD3+CD8+ T-cells increased. Following vaccination with either species, parasite migration was apparently delayed in the skin and interrupted at the lungs, the lymphnodes gained weight, and cell numbers of axillary lymph nodes increased more than after infection. In mediastinal lymphnodes, only immunization with S. japonicum but not S. mansoni cercariae led to an increase of CD3+CD4+ T-cells. Following infection, both schistosome species induced higher CD3+CD4+, but not CD3+CD8+ T-cells in mediastinal nodes, and the peak was earlier with S. japonicum (about seven days after infection) than with S. mansoni (about 10 days). In analogy to T-cell observations by others using a gamma-attenuated cercarial vaccine in S. mansoni, the present results suggest that CD3+CD4+ cells also play a role in the ultraviolet-attenuated vaccine against S. japonicum.